2021
DOI: 10.1111/jcmm.16333
|View full text |Cite
|
Sign up to set email alerts
|

Role of sphingosine‐1‐phosphate receptors in vascular injury of inflammatory bowel disease

Abstract: Sphingosine‐1‐phosphate receptors (S1PRs) have an impact on the intestinal inflammation of inflammatory bowel disease (IBD) by regulating lymphocyte migration and differentiation. S1PR modulators as an emerging therapeutic approach are being investigated for the treatment of IBD. However, the role of S1PRs in intestinal vessels has not drawn much attention. Intestinal vascular damage is one of the major pathophysiological features of IBD, characterized by increased vascular density and impaired barrier functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…[ 17 ] Studies have shown that S1PR1 expression changes dynamically when endothelial cells are activated, injured, or inflamed. [ 18 ] Therefore, the mechanism underlying the rapid and excellent targeting effect of the S1P@CD‐PLGA NBs on inflammatory vascular endothelial cells was further studied. First, according to the Western blot qualitative results in Figure a and quantitative results in Figure 5b of S1PR1 protein expression in both normal rat carotid endothelial cells and histamine‐induced inflammatory rat carotid endothelial cells, it was found that histamine‐induced inflammatory vascular endothelial cells expressed more S1PR1 than normal endothelial cells, which showed a 1.35‐fold enhancement in S1PR1 level ( p = 0.0079).…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] Studies have shown that S1PR1 expression changes dynamically when endothelial cells are activated, injured, or inflamed. [ 18 ] Therefore, the mechanism underlying the rapid and excellent targeting effect of the S1P@CD‐PLGA NBs on inflammatory vascular endothelial cells was further studied. First, according to the Western blot qualitative results in Figure a and quantitative results in Figure 5b of S1PR1 protein expression in both normal rat carotid endothelial cells and histamine‐induced inflammatory rat carotid endothelial cells, it was found that histamine‐induced inflammatory vascular endothelial cells expressed more S1PR1 than normal endothelial cells, which showed a 1.35‐fold enhancement in S1PR1 level ( p = 0.0079).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, increased VEGF levels and MPO activity were noted in the colonic tissues of DSS-treated mice. Elevated VEGF expression has been linked directly to pathological angiogenesis and inflammation in both human and experimental colitis [ [ 34 ]]. Rutin markedly downregulated VEGF expression levels and MPO activity, suggesting its potential role in protecting vascular endothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…CD62L is essential for T cell adhesion, facilitating lymphocyte homing to secondary lymphatic organs. In contrast, CD69 serves a dual role: it counters the sphingosine-1-phosphate receptor, which typically signals to T cells to move into the bloodstream, and acts as a T cell activation marker [ 149 , 150 , 187 , 188 , 189 ]. Bovine T-IELs express low levels of CD62L and high levels of CD69, a pattern also observed in humans and mice [ 61 , 190 ].…”
Section: Discussionmentioning
confidence: 99%